Narrative, metaphor and the subjective understanding of historic identity transition. Issue 8 (17th November 2017) - Maclean, Mairi; Harvey, Charles; Stringfellow, Lindsay
Abstract: This article examines the relevance of employing an oral history method and narrative interview techniques for business historians. We explore the use of oral history interviews as a means of capturing the expression of subjective experience in narrative and metaphor. We do so by analysing interviews concerning the transition of East German identities following reunification with West Germany. Self-expression emerges as critical to the vital identity work required for social integration following transformation, metaphor providing a means of articulating deep-rooted patterns of thought. We demonstrate that employing an oral history methodology can benefit business historians by affording access to the human dimension of a research project, unlocking the subjective understanding of experience by low-power actors among the non-hegemonic classes. Hence, employing an oral history methodology provides a valuable means of countering narrative imperialism, exemplified here by the dominant West German success story grounded in Western-style individual freedom.